Allyl ether of mansonone G as a potential anticancer agent for colorectal cancer - Savinee Chanvijit; Suttinee Phuagkhaopong; Panupong Mahalapbutr; Methus Klaewkla; Warinthorn Chavasiri; Piyanuch Wonganan (Scientific Reports, 2022)
Abstract Mansonone G (MG), a 1,2-naphthoquinone isolated from the heartwood of Mansonia gagei Drumm, exhibited several pharmacological activities such as anti-bacterial, anti-estrogenic and anti-adipogenic effect. This study evaluated the cytotoxicity of MG and its derivatives as well as determined the mechanism(s) underlying the cytotoxic activity of the most potent MG derivative on two CRC cell lines, HCT-116 cells carrying p53 wild-type and HT-29 cells carrying p53 mutant. We found that MG and its derivatives could inhibit viability of HCT-116 and HT-29 cells in a concentration-dependent manner. Of all semi-synthetic derivatives of MG, allyl ether mansonone G (MG7) was the most potent cytotoxic agent toward cancer cells and less toxic to normal cells. MG7 could induce ROS generation which was associated with cytotoxicity and apoptosis in both HCT-116 and HT-29 cells. Western blot analysis revealed that MG7 downregulated the expression of Bcl-2 and Bcl-xL proteins in both CRC cell lines and upregulated the expression of BAK protein in HT-29 cells. Moreover, MG7 inhibited AKT signaling pathway in both CRC cell lines and modulated ERK1/2 signaling pathway by inhibiting ERK1/2 phosphorylation in HCT-116 cells and activating ERK1/2 phosphorylation in HT-29 cells. Molecular docking revealed that MG7 could bind to the ATP-binding pocket of AKT and ERK1 via hydrophobic interactions.